REPRODUCTION PERFORMANCE OF HUMPBACK GROUPER (Cromileptes altivelis) FROM WILD BROODSTOCK (F-0), FIRST GENERATION BROODSTOCK (F-1), AND SECOND GENERATION BROODSTOCK (F-2) - Tridjoko Tridjoko (Jurnal Ilmu dan Teknologi Kelautan Tropis, 2010)
Grouper seeding technology still relies on the broodstock from the ocean, eventhough, the existence of the broodstock is rare and difficult to obtain. The broodstock takes a long time to mature and spawn. Therefore, to anticipate the scarcity humpback grouper from wild, it is important to produce broodfish from aquaculture. This study was aimed to know the reproduction performance of humpback grouper wild broodstock F-0, first generation broodstock (F-1) and second generation broodstock (F-2). The cultured of humback grouper broodstock used three tanks 75 m3 in volume (tank I, II and tank III). Tank I: reared 35 fishes broodstock F-0. Tank II and tank III for reared each 50 fishes F-1 and F-2 broodstock. Food for broodstock from the wild (F-0) was given from fresh trash fish, squid, and added vitamin mixture, vitamin C and vitamin E. Meanwhhile, food given to F-1 and F-2 broodstock was a commercial dry pellet (PG 9-10) that contains following nutrients: protein content of 43%, min. fat of 9%, ash content of 13%, fiber levels of 2%, and moisture content of 12%. Mixture of vitamin C and E were also added. The results showed that the humpback grouper F-0, F-1 and F-2 were cultured in 75 m3 concrete tank was successfully spawn with the fertilization rate of 87%, 78% and 45% respectively. This result proves that the broodstock from F-0 gaved the best results.Keywords: Humpback grouper reproduction, wild broodstock (F-0), first generation (F-1), seccond generation (F-2)